Diversity of human papillomavirus in the anal canal of HIV-positive and HIV-negative men. Issue 1 (January 2021) - Galati, Luisa; Brancaccio, Rosario N.; Gupta, Purnima; Lohmann, Eugenie; Robitaille, Alexis; Mandishora, Racheal S. Dube; Cuenin, Cyrille; Filotico, Raffaele; Combes, Jean-Damien; Giuliano, Anna R.; Donà, Maria Gabriella; Tommasino, Massimo; et al.
Highlights: Mucosal and cutaneous human papillomaviruses are abundantly present in the anal canal. Different risk factors influence the distribution of specific HPV genera in the anal canal. Next-generation sequencing-based protocols resulted in the identification of novel putative HPV types. Summary: Background: To characterize the HPV diversity in the anal mucosa of men with different sexual behavior and HIV status by next-generation sequencing (NGS). Methods: Anal swabs from HIV-positive ( n  = 94; mean age, 38 years) and HIV-negative ( n  = 100; mean age, 37.5 years) men who have sex with men (MSM) and HIV-negative men (predominantly men who have sex with women, MSW) ( n  = 99; mean age, 38.2 years) were analyzed by broad-spectrum PCR protocols combined with NGS. Findings: Alpha HPV types ( n  = 74) were detected mainly in the MSM groups (HPV6, 11, and 43 were the most abundant types) compared with MSW ( n  = 16) (HPV11, 32, and 87 were among the most abundant). In contrast, beta HPVs were more abundantly detected among MSW ( n  = 45) than in the HIV-positive ( n  = 16) and HIV-negative ( n  = 26) MSM groups. Gamma HPVs were detected almost equally in HIV-positive MSM ( n  = 62), HIV-negative MSM ( n  = 58), and MSW ( n  = 57). In addition, 31 putative novel PV types were identified. Conclusions: Our data show that beta and gamma HPV types are present in the anal mucosa, thus reinforcing the existing evidence that they can be detected at anatomical sites other than skin. Alpha and beta HPV distribution among these three groups appears to vary according to sexual behavior.